Impact of 1-week preoperative auto-CPAP treatment on postoperative outcomes in patients undergoing heart valve replacement surgery: a prospective randomized controlled trial - Su, Mei; Lin, Wei; Xu, Qi; Ni, Buqing; Zhang, Xilong; Zhang, Shijiang; Ding, Ning (Frontiers in Neurology, 2023)
Background Whether preoperative continuous positive airway pressure (CPAP) treatment improves postoperative outcomes in patients undergoing cardiac valve replacement (CVR) remains unknown. Hypothesis This study was to evaluate the effects of 1-week perioperative auto-continuous positive airway pressure (CPAP) treatment on postoperative heart and pulmonary outcomes in patients with obstructive sleep apnea (OSA) and valvular heart disease. Methods Thirty-two patients with OSA and valvular heart disease were randomly assigned to 1-week CPAP (n = 15) group and non-CPAP treatments (n = 17) group. After the treatment, all patients underwent CVR surgery. The length of ICU and hospital stays, postoperative cardiac and respiratory complications were assessed and compared between the 2 groups. Results The results showed there was no significant difference in the baseline characteristics between the CPAP and non-CPAP treatment groups. The length of postoperative ICU and hospital stays, as well as the duration of mechanical ventilation were significantly reduced in the CPAP treatment group compared to the non-CPAP treatment group; however, there were no significant differences in cardiac complications (postoperative arrhythmias, pacemaker use, first dose of dopamine in the ICU, and first dose of dobutamine in the ICU), and respiratory complications (reintubation and pneumonia). Conclusion We concluded that in patients underwent CVR, preoperative use of auto-CPAP for OSA significantly decreased the duration of mechanical ventilation, and postoperative stays in the ICU and hospital. Clinical Trial Registration: https://ClinicalTrials.gov, identifier NCT03398733.